Theoretical advances and problems in the sociology of punishment - Garland, David (Punishment & society, 2018)
The last twenty years have seen a remarkable increase in the extent and range of “punishment and society” scholarship. Together with this quantitative expansion, there have also been important qualitative developments in research, analysis and explanation - many of which can be counted as scientific advances. This article specifies a number of dimensions along which theory, method and data in this field have been improved and also identifies some continuing challenges and problems. Examples from the literature on the emergence of “mass incarceration” and the nature of the “war on drugs” are used to indicate the range of theoretical resources that scholars in this field have developed and to point to empirical and theoretical questions that remain to be resolved.